2017
DOI: 10.1519/jsc.0000000000001506
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Accelerometer Derived Impacts Associated With Competitive Games in National Collegiate Athletic Association Division I College Football Players

Abstract: Wellman, AD, Coad, SC, Goulet, GC, and McLellan, CP. Quantification of accelerometer derived impacts associated with competitive games in National Collegiate Athletic Association division I college football players. J Strength Cond Res 31(2): 330-338, 2017-The aims of the present study were to (a) examine positional impact profiles of National Collegiate Athletic Association (NCAA) division I college football players using global positioning system (GPS) and integrated accelerometry (IA) technology and (b) det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…In addition, one should also consider the multifactorial nature of injuries and recognise that training workloads represent only one of a number of extrinsic and intrinsic risk factors that influence the risk of injury 28 . Correspondingly, given large mass and BMI differences and the known variance in workload previously across the positional groups, 17,18 a more in-depth assessment of injury risks relative position is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one should also consider the multifactorial nature of injuries and recognise that training workloads represent only one of a number of extrinsic and intrinsic risk factors that influence the risk of injury 28 . Correspondingly, given large mass and BMI differences and the known variance in workload previously across the positional groups, 17,18 a more in-depth assessment of injury risks relative position is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…16 Interestingly Malone and colleagues also showed that first year players were less able to tolerate ACWR spikes. 16 However, whilst it is also known that NCAA football workloads are highly variable relative to positional demands, 17,18 ACWR-injury risks in American football have yet to be determined. This investigation will therefore examine workload injury risk relationships in NCAA football.…”
Section: Introductionmentioning
confidence: 99%
“…Within the offensive groups, WR's sustained more 5-6.5 G force impacts (moderate to light) than other position groups, whereas RB's were found to endure the most severe (>10 G force) impacts bar the QB's. DB's and LB's absorbed more very light (5.0-6.0 G force) impacts, and defensive tackles (interior DL) reported significantly more heavy and very heavy (7.1-10 G force) impacts than other defensive positions 13 . These studies further our understanding of the demands imposed on players, which may form the basis for the design of position-specific monitoring and training in the preparation for the external load and impact forces performed in games.…”
Section: The Physiological Demands Of Afmentioning
confidence: 92%
“…Scientific studies on collegiate AF have grown exponentially since the first paper in 1969, leading to various avenues of scientific development in key areas from this time to the present day. These include injury prevention 3,4 , concussion 5 , return to play injury characteristics 6,7 , analysis of strength and conditioning [8][9][10][11] , overall health 12 and wellbeing and most recently the objective quantification of training and games [13][14][15] .…”
Section: Conceptual Introductionmentioning
confidence: 99%
“…In soccer, the detection threshold is 5G, and the number of impacts ranges from 490±309.5 to 613.1±329.4 number of impacts [42]. In trying score games, a greater number of >5G impacts were found in rugby 895±325 [102], rugby union 1222±607 [103] and American football 951 ±192 [99]. This difference could be due to the lower intensity of physical contacts in soccer (disputes, tackles, charges) compared with rugby or American football (collisions, scrum, rucks, etc.…”
Section: Accelerometry-based Workload Indexesmentioning
confidence: 99%